2015
DOI: 10.1016/j.carbon.2015.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Reducing and multiple-element doping of graphene oxide using active screen plasma treatments

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
(60 reference statements)
1
18
0
Order By: Relevance
“…This feature can be assigned to multiple bonds of carbon with nitrogen and with the different bonds with oxygen. Another similar study using XPS to analyze the composition and chemical state of GO treated by H 2 plasma and a gas mixture of H 2 and N 2 was done by Chen et al Various identified carbon‐oxygen bonds, CO in COH, epoxy type COC, carbonyl type CO, and carboxylic type O(CO), are similar to our results. The work also suggests CO is unstable which can be reduced by effective plasma treatment.…”
Section: Resultssupporting
confidence: 90%
“…This feature can be assigned to multiple bonds of carbon with nitrogen and with the different bonds with oxygen. Another similar study using XPS to analyze the composition and chemical state of GO treated by H 2 plasma and a gas mixture of H 2 and N 2 was done by Chen et al Various identified carbon‐oxygen bonds, CO in COH, epoxy type COC, carbonyl type CO, and carboxylic type O(CO), are similar to our results. The work also suggests CO is unstable which can be reduced by effective plasma treatment.…”
Section: Resultssupporting
confidence: 90%
“…Four different O functional groups as well as a contribution of adsorption oxygen are identified. The peak at 529.7 eV corresponds to oxygen ions (O a ) bonded to Fe cations in a coordinatively saturated environment (Fe═O); the peak at 530.4 eV corresponds to oxygen atoms in keto and quinone groups (C═O); the peak at 531.5 eV corresponds to the K―O bonds; the peak at 532.2 eV corresponds to the oxygen atoms bond to carbon atoms in form of single bond (C―OH or C―O―C); and the peak at 533.1 eV corresponds to the single bonded oxygen in carboxylic group (O―C═O) …”
Section: Resultsmentioning
confidence: 99%
“…The GO coatings can be produced by chemical methods [23], dissolving graphene powder and other salts in sulfuric acid, subsequently dispersing and exfoliating the GO nanosheets by sonication, and finally casting it onto the substrate. A reduction process is then required to remove the oxygen functionalities and obtain a graphene coating of high quality, and the ASP technology was used for this purpose [24]. The ASP treatments were conducted at 400 Pa in pure H 2 or N 2 -H 2 mixtures, at temperatures between 100 and 200°C for 1 h. The appearance of coatings changed from a light brown color to silver-gray after the plasma reduction in pure hydrogen and nitrogen-hydrogen mixtures, and this change was accompanied by a decrease in optical transparency and electrical resistance of the coating (Figure 2.3).…”
Section: Reduction Of Graphene Oxide For Optoelectronic Devicesmentioning
confidence: 99%